Hypoxic Regulation of Neutrophils in Cancer - Triner, Daniel (Int J Mol Sci, 2019)
Neutrophils have been well-characterized for their role in the host anti-microbial response. However, it is now appreciated that neutrophils have a critical role in tumorigenesis and tumor progression in the majority of solid tumors. Recent studies have indicated a critical role for hypoxia in regulating neutrophil function in tumors. Furthermore, neutrophil-specific expression of hypoxia-inducible transcription factors may represent a novel therapeutic target for human cancer. In this review, we highlight the function of neutrophils in cancer and the role of the neutrophil hypoxic response in regulating the neoplastic progression of cancer.